Cultural engagement and prevalence of pain in socially isolated older people: a longitudinal modified treatment policy approachResearch in context - Takahiro Miki; Upul Cooray; Masashi Kanai; Yuta Hagiwara; Takaaki Ikeda (EClinicalMedicine, 2024)
Summary: Background: It remains uncertain whether cultural engagement positively influences the reduction of pain risk, particularly depending on the social isolation status. The aim of this study was to examine the impact of cultural engagement on the reduction of pain prevalence over a 6-year follow-up period among older people, particularly those experiencing different dimensions of social isolation. Methods: This study was a prospective longitudinal study. We analysed the English Longitudinal Study of Ageing cohort, consisting of 6468 community-dwelling adults aged ≥50 years old who provided data in waves 6 (2012–2013), 7 (2014–2015), 8 (2016–2017), and 9 (2018–2019). Self-reported cultural engagement (going to museums, art galleries, exhibitions, the theatre, concerts, or the opera) measured in waves 6–8 was used as the exposure variable. Meanwhile self-reported moderate-to-severe pain in wave 9 was used as the outcome variable. Social isolation was considered in waves 6–8, and the possibility of effect modification was captured by assessing each component of the social isolation index: not married or cohabiting with a partner, fewer than monthly contact with children/other immediate family/friends, and not engaging in any organisations, religious groups, or committees. Findings: The estimated pain prevalence was 29.2% (95% confidence interval, 28.1–30.3; reference) after adjusting for time-variant, time-invariant, and loss to follow-up factors. Cultural engagement led to a reduction in pain prevalence to 24.1% for all individuals, representing a decrease of 5.1% (95% confidence interval, 0.6–9.6; P-value, 0.03). In older people who were not married or cohabiting, cultural engagement resulted in a decrease in pain prevalence to 25.8%, a reduction of 3.4% (95% confidence interval, 0.4–6.4; P-value, 0.01). For those with less frequent contact with close family members, the pain prevalence decreased to 25.3%, a reduction of 3.9% (95% confidence interval, 0.2–7.6; P-value, 0.03). Meanwhile, other dimensions of social isolation did not show a significant reduction in pain prevalence. Interpretation: Cultural engagement may help to reduce the risk of pain in socially isolated older adults. Those who were single or living alone and had less frequent contact with immediate family were particularly vulnerable. While cultural engagement might help certain socially isolated older people feel better, its effectiveness varies, highlighting the need for targeted interventions. Funding: The Japan Society for the Promotion of Science (JSPS) KAKENHI Grant Number (22K17648, Ikeda).